Treatment Non-Compliance In Patients Suffering From Schizophrenia And Bipolar Affective Disorder (BPAD): A Comparative Study - Paudel, K.; Subedi, S. (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Non-adherence to appropriately prescribed medication for psychiatric disorders prevents patients from realizing the full benefits of their treatment and negatively impacts on individuals, their families and the healthcare system. Understanding and reducing non-adherence is therefore a key challenge to quality care for patients with psychiatric disorders. This finding highlights the prevalence, consequence of non-adherence and barriers to adherence. Therefore, the main objective of this study was to determine the incidence and factors associated with medication non-compliance among patients suffering from schizophrenia and bipolar affective disorders. Material and Method: This cross-sectional study included 94 schizophrenia and 76 bipolar affective disorder subjects who were visited psychiatric OPD of tertiary level hospital and disproportionate stratified random sampling method. An anonymous socio-demographic as well contributing factor questionnaire pre tested, semi structured pro forma by interview method and a clinical proforma designed by Morisky, the 8-item Morisky Medication Adherence Scale (MMAS-8) were used for data collection. Results: The prevalence of non-compliance was 88%, the independent predictors of non-compliance were; seeking for traditional/spiritual treatment, weight gain as side effects of drugs , increased number of medication (p=0.038), beginning of medication start (p=0.057), unemployment (p=0.059), low level of insight/education (p=0.044), male as gender (p=0.016). Conclusion: Based on the outcome of the study, we recommend the development of psycho-educational programmes on compliance and the active involvement of the relatives and significant others in the management of patients of mentally ill patients.